Phenotypic characterization of Jaunpuri goat of Uttar Pradesh - A K Patel; VK Singh; Jaswant Singh; N Shyamsana Singh; M K Verma (Journal of Livestock Biodiversity, 2025)
The present study was conducted in two district of eastern Uttar Pradesh viz. Faizabad and Jaunpur. Sevenv illages from Faizabad and eight villages from Jaunpur have been randomly selected. 17 farmers and 140 goats from Faizabad and 15 farmers and 143 goats from Jaunpur district were selected for present investigation. Dataon growth performance and physical characteristics were recorded on 293 Jaunpuri goats of various age groups in its two native districts viz., Jaunpur and Faizabad of Eastern U.P. during 2009-20110. The average body weights of the age groups 0-3, 6-9 and 12-24 months were 4.89±1.02, 15.45±0.30 and 20.44±0.49 kg, respectively. In these respective age groups the mean values (cm) of body length were 32.69±1.85, 43.65±0.52 and 46.34±0.49; chest girth: 38.54±2.27, 55.67±0.77 and 60.91±0.58 and height: 37.69±1.66, 58.38±0.88 and 60.80±0.65 respectively. The findings indicated that Jaunpuri goat is a medium size goat breed and the roman nose is distinct trait of this population.